Costs of acute stroke care on regular neurological wards: a comparison with stroke unit setting - Epifanov, Yaroslav; Dodel, Richard; Haacke, Caroline; Schaeg, Matthias; Schöffski, Oliver; Hennerici, Michael G.; Back, Tobias (Health policy, 2007)
OBJECTIVES: Stroke unit care has been shown to be beneficial but costly. In an own previous study, the resource utilization of stroke unit care has been evaluated. Since the resource utilization on regular neurological wards is widely unknown, we determined the costs for acute stroke care on regular neurological wards to compare both treatment settings. - METHODS AND PATIENTS: We included 253 consecutive in-patients with the diagnosis of ischemic stroke (IS), intracerebral hemorrhage (ICH) or transient ischemic attack (TIA) treated on regular wards at a German University Department of Neurology, between 1 January and 30 June 1998. The modified Rankin scale (mRS) was used to assess outcome. Costs of stroke care were calculated from the perspective of the healthcare provider (hospital) by using a bottom-up approach. Resource utilization was compared to stroke unit care as determined in a previous study. Prices of 2002 were used (in Euros). - RESULTS: IS was present in 78% (n=196), TIA in 13% (n=34), and ICH in 9% (n=23) of patients. Length of stay was 11.1+/-8.9 (mean+/-S.D., IS), 11.1+/-6.5 (TIA), and 16.9+/-15.5 (ICH) days (p>0.05). Mean costs of stroke care were euro 3060 (US$ 3180) for TIA, euro 3070 (US$ 3200) for IS and euro 5210 (US$ 5430) for ICH (p<0.05, ICH versus IS and TIA). The highest costs were due to non-medical care (46%) and personnel (25%). The mRS improved during hospitalization from 3.0+/-1.6 to 2.2+/-1.8 (p<0.01). Compared to care on regular neurological wards, mean costs per admission with treatment on stroke units increased by 7.0%, mean costs per day by 15.6%. - CONCLUSION: The comparison - considering a potential bias of patient selection - shows that acute stroke unit care is approximately 16% more costly than treatment on regular neurological wards due to higher resource use of personnel and diagnostic procedures. Stroke unit treatment tends to decrease post-acute in-patient care costs.
Available online 22 August 2006
Gesehen am 25.04.2022